Sport Management, Innovation and the COVID-19 Crisis - Ersoz, Gozde; Yenilmez, Meltem Ince (Routledge Research in Sport Business and Management, 2023)
This book looks at how sport, and sports organisations, have had to innovate during the COVID-19 pandemic. Against a backdrop of lockdowns, empty stadia and a fast-moving public health crisis, the book presents fascinating case studies of innovation and crisis management in sport, with valuable lessons to be learned for preparedness and resilience in future crises. The book explores how managerial processes have evolved during the pandemic in areas as diverse as sports communication, youth sport, sports events, esports, sports tourism, and physical activity, in both professional and community settings. It considers the fundamental importance of technology as a tool of innovation, and considers how different stakeholder groups, from governing bodies to athletes to fans, have developed new pathways of engagement and what that might mean for the future development of the sport industry. This is fascinating reading for any student, researcher, practitioner or policy maker looking to better understand this profound moment in the history of sport and society, and to anybody with an interest in key themes in sport business and management, such as innovation, crisis management or consumer behaviour.